2020
DOI: 10.9778/cmajo.20200159
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and clinical practice in patients with COVID-19 admitted to the intensive care unit in Montréal, Canada: a descriptive analysis

Abstract: (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in December 2019. As of Nov. 13, 2020, millions of infections have occurred, and COVID-19 has claimed more than 1.3 million lives, with an overall mortality rate of about 3% and mortality of up to 60% in the critically ill. 1-6 Limited information is available to describe the outcomes of patients admitted to intensive care units (ICUs) in Canada. The Jewish General Hospital was the first designated pandemic centre for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Another multicenter study conducted in Germany found a SOFA score of 5 (3–9), with a mortality rate of 35% (78 out of 223) [ 29 ]. A retrospective study in Canada reported a SOFA score of 5 (3–8), and 18 patients died out of 106 (17%) admitted [ 39 ]. Therefore, both SOFA and quick SOFA scores are useful tools for predicting mortality among ICU patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Another multicenter study conducted in Germany found a SOFA score of 5 (3–9), with a mortality rate of 35% (78 out of 223) [ 29 ]. A retrospective study in Canada reported a SOFA score of 5 (3–8), and 18 patients died out of 106 (17%) admitted [ 39 ]. Therefore, both SOFA and quick SOFA scores are useful tools for predicting mortality among ICU patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The median [IQR] age was 66 [59-73] yr, and 44% were classified as obese. Patients had a median [IQR] SpO 2 /F I O 2 ratio of 120 [94-164], and a median [IQR] 4C score of 12 [10][11][12][13][14]. Full demographic, clinical, and treatment information is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Results One hundred and forty-two patients were analysed, with a median [interquartile range (IQR)] age of 66 [59-73] yr; 71% were male. Patients had a median [IQR] Sequential Organ Failure Assessment Score of 3 [2][3], median [IQR] oxygen saturation by pulse oximetry/ fraction of inspired oxygen ratio of 120 , and a median [IQR] 4C score (a COVID-19-specific mortality score) of 12 [10][11][12][13][14]. Endotracheal intubation occurred in 48/142 (34%) patients, and overall hospital mortality was 16%.…”
Section: Introductionmentioning
confidence: 99%
“…We performed a MEDLINE search from inception to 3 January 2021 using the following keywords: ‘COVID-19’, ‘Intensive Care’ and ‘Canada’, and found three observational studies describing COVID-19 ICU outcomes in Canada [ [2] , [3] , [4] ]. The studies were published between May and November 2020, describe patients in Canada during the first wave of the Canadian COVID-19 pandemic, and satisfy all of the authors inclusion criteria.…”
mentioning
confidence: 99%
“…[ 3 ] Yang et al. [ 4 ] Age (years) 69 62 66 Male 79 (68%) 50 (67%) 64 (60%) Sample size 117 75 106 NIV 15 (13%) 16 (21%) 0 (0%) HFNO 43 (37%) 2 (3%) 51 (48%) IMV 74 (63%) 43 (57%) 65 (61%) ECMO 3 (3%) 1 (1%) 0 (0%) RRT 16 (14%) 7 (9%) 12 (11%) Vasopressors 65 (56%) NA NA ICU LOS (days) 9 10 10 ICU mortality 18 (15%) 17 (23%) 18 (17%) ICU mortality if IMV used 15 (20%) 8 (19%) 12 (19%) Hospital mortality 30 (26%) 19 (25%) 21 (20%) Abbreviations: COVID-19, coronavirus disease 2019; ECMO, extracorporeal membrane oxygenation; HFNO, high-flow nasal oxygen; IMV, invasive mechanical ventilation; LOS, length of stay; NIV, non-invasive ventilation; RRT, renal replacement therapy. …”
mentioning
confidence: 99%